Synthesis and characterization of ultrafine CeO2 particles by glycothermal process - Bae, DS; Lim, B; Kim, BI; Han, KS (ELSEVIER SCIENCE BV, 2002)
The cerium oxide nanosize particles were prepared under mild temperature and pressure conditions by precipitation from metal nitrates with aqueous potassium hydroxide. Various types of cerium oxide powders were obtained at 200-230degreesC. The average size of synthesized particles was in the range of 10-50 nm and the phase of synthesized particles was crystalline. The effects of synthesis parameters, such as the concentration of starting solution, pH of starting solution, reaction temperature and time, are discussed. (C) 2002 Elsevier Science B.V. All tights reserved.
Keywords: CERIUM(IV) OXIDE